2015
DOI: 10.2146/ajhp130797
|View full text |Cite
|
Sign up to set email alerts
|

Antiinfective therapy for pregnant or lactating patients in the emergency department

Abstract: The use of antiinfective agents in pregnant or lactating women requires consideration not only of the drugs' effectiveness but also their possible effects on the fetus or newborn and the nature of follow-up care. References are available to help clinicians make treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It must also be acknowledged that, while the overuse of antibiotics can promote antimicrobial resistance and microbiome dysbiosis, untreated infections can also be harmful, especially to a developing fetus. For example, urinary tract infections during pregnancy are associated with intrauterine growth restriction, preterm labour and miscarriage [40,41]. Keeping this risk-benefit balance in mind, it is important to study and clarify the potentially unintended consequences of prenatal antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be acknowledged that, while the overuse of antibiotics can promote antimicrobial resistance and microbiome dysbiosis, untreated infections can also be harmful, especially to a developing fetus. For example, urinary tract infections during pregnancy are associated with intrauterine growth restriction, preterm labour and miscarriage [40,41]. Keeping this risk-benefit balance in mind, it is important to study and clarify the potentially unintended consequences of prenatal antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The most common infections encountered during pregnancy include urinary tract infections (UTIs), including pyelonephritis; sexually transmitted infections (STIs); and upper respiratory tract infections (URTIs) . Although use of any medication during pregnancy is a risk‐versus‐benefit decision, untreated infections such as UTIs or STIs are associated with significant fetal risk including spontaneous abortion, prematurity, and low birth weight . Safety and efficacy information are not usually available from randomized controlled trials, as these studies are often not feasible in pregnant women and are potentially unethical.…”
Section: Food and Drug Administration Pregnancy Category Ratings Withmentioning
confidence: 99%
“…Protein binding ranges from 20% to 50% . Fluoroquinolones may be safe during the first trimester but are not recommended, as they were associated with fetal harm in previous animal studies There is a suggested association with fluoroquinolones and renal toxicity, cardiac defects, and central nervous system toxicity in the fetus . Animal data have demonstrated bone and cartilage damage in the fetus .…”
Section: Fluoroquinolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anticipated that up to 30% of women will receive a course of antibiotics during pregnancy for a confirmed or presumed bacterial infection, most commonly UTIs, URTIs, or STIs. [94][95][96][97] CPGs, if available, often include limited sections on management of bacterial infections in pregnancy. This review provides the clinician with a resource for management of common viral and bacterial infections in pregnancy for both patient care decision making and trainee instruction.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%